The experiences of award-winning women community college presidents achieving equitable education outcomes - Ross, Elizabeth A. (My University, 2025)
This narrative inquiry examines the experiences of award-winning women community college presidents recognized by Achieving the Dream, Inc. (ATD) for their leadership in achieving equitable education outcomes. In a polarized political climate and growing efforts to erase diversity, equity, and inclusion initiatives in America, this study explores how these leaders navigate institutional challenges and implement change initiatives that address persistent equity gaps in community colleges. Drawing on transformational leadership theory, the study highlights the strategies, obstacles, and successes that shape the presidents' leadership practices. Through in-depth interviews, analysis of institutional documents, and by centering the personal narratives of women who demonstrated exceptional commitment to equity, this study contributes valuable insights into the leadership dynamics of community colleges and offers actionable recommendations for fostering inclusive environments. The findings emphasize the critical role these leaders play in promoting equity and inclusion, ensuring all students have equal access to opportunities, and advancing inclusive practices despite political and societal pressures. This dissertation contributes to the literature on higher education leadership, particularly in community colleges, by offering a deeper understanding of how women presidents are leading efforts to close equity gaps amid ongoing challenges to diversity, equity, and inclusion.
Keywords: Women community college presidents; Equitable education outcomes; Transformational leadership; Community college CEOs; Female community college presidents